Prevalence of Cardiovascular risk factors among the residents of urban community of Kathmandu municipality - Bogati, Amrit; Manandhar, Reeju; Sharma, Deewakar; Baidhya, Sajan G.; Prajapati, Dipanker; Baniya, Sebina; Bista, Neha; Khanal, Sagun; Ranabhat, Sudha (Nepalese Heart Journal, 2017)
Background and Aims: The prevalence of risk factors for cardiovascular diseases is globally increasing leading to the increase in mortality and morbidity due to cardiovascular diseases. The objective of this study is to assess the prevalence of cardiovascular risk factors among the residents of urban community of Kathmandu municipality.Methods: By using simple random sampling method, we selected 130 participants aged 18 years or above, from the voters list of ward no.22 of Kathmandu. Male participants aged less than 45 and female participants aged less than 55 were grouped as young age group which included total of 80 (61.5%) participants and rest were grouped as old age group. All the participants gave the informed consent. Statistical analysis was done using SPSS software version 20.Results: The mean age of the participants was 46.6 years with 53.8% male. Insufficient physical activity (68.5%), high waist circumference (67.7%) were the two most prevalent risk factors followed by obesity (59.2%), hypertension (37.7%), tobacco consumption (37.5%), dyslipidemia (22.3%) and diabetes (16.9%) in overall population. Tobacco consumption were more prevalent in male participants of both younger and older age groups whereas high waist circumference was prevalent in female participants of both age group.Conclusion: Our study showed high prevalence of insufficient physical activity, high waist circumference, obesity, hypertension and tobacco use among urban population of Kathmandu, suggesting possibility of higher incidence of cardiovascular disease in future, pointing towards the need of aggressive preventive strategy to prevent epidemic of cardiovascular disease.Nepalese Heart Journal 2017; 14(1): 3-7